Nutritional Evaluation of Azolla microphylla Meal and its Effect on Nutrient Digestibility and Growth Performance in Crossbred Cattle - Arvindraj, N.; Chatterjee, A.; Ghosh, M. K.; Das, S. K.; Dutta, T. K. (Indian Journal of Animal Nutrition, 2017)
The effect of inclusion of azolla meal in the ration on growth performance and nutrient digestibility was studied in crossbred cattle. Azolla meal was a good source of protein (25%). The contents of CF, EE, total ash, NFE, NDF, ADF and ADL in Azolla microphylla meal were 12.62, 4.06, 19.87, 38.37, 68.43, 37.60 and 16.22, respectively. A growth trial of 105 days was conducted on 10 cross bred male calves distributed into two groups of 5 animals each (T0 and T1). A digestibility trial of six day collection was conducted towards the end of theexperiment. The animals in control group (T0) were offered paddy straw (45%), green fodder (15%) and concentrate mixture (40%). In the treatment group (T1) dried A. microphylla meal was supplemented @ 60 g/ animal (equivalent to 1 kg fresh azolla) replacing 10% of concentrate mixture fed to the calves. There was no significant difference in total DM, CP, TDN intakes and digestibility of nutrients between two groups. The feed conversion efficiency (kg live weight gain/ 100 kg DMI) was higher (P